The Francis Ford Coppola encyclopedia - Welsh, James Michael (Scarecrow Press, 2010)
The entries in this encyclopedia focus on all aspects of Copppola's work, from his early days with producer Roger Corman to his films as the director of the 1970s. This extensive reference contains material on all of the films Coppola has played a role in, from screenwriter to producer to director, including such classics as Patton, The Godfather, The Conversation, The Godfather Part II, and Apocalypse Now. Each entry is followed by a bibliography of published sources, both in print and online. --from publisher description.